Metode Bimbingan Konseling Islami dalam Mencegah Perilaku Agresif pada Anak Berkebutuhan Khusus di Athaya Medan - Hanifah, Fathwa (Comit: Communication, Information and Technology Journal, 2024)
This research is entitled "Islamic Counseling Guidance Methods in Preventing Aggressive Behavior in Children with Special Needs at Athaya Medan". The aim of this researh is to find out how Islamic counseling guidance methods are carried out in the process of preventing aggressive behavior in children with special needs, the inhibiting factors in the process of implementing Islamic counseling guidance, the impact of the results of Islamic counseling guidance, and the solutions to the aggressive behavior problems experienced by children with special needs at Athaya Medan. This researh is a field study with qualitative research. The research informants in this study are the Founder of ABK Athaya and also the counselor for children with special needs. Data collection for this research uses interview, observation, and documentation methods. Primary data sources are obtained from related research informants and secondary data sources are obtained from documentation, books, or literature related to this research. Data analysis techniques in this study include data reduction, data presentation, and conclusions. The results of this study show that the Islamic counseling guidance carried out by counselors for children with special needs includes therapy, learning to read Arabic letters, brain training skills, and playing with motor/educational toys. Children with special needs are also encouraged to do muhasabah (evaluate, reflect on the essence of themselves, and their attitudes and behaviors at present, which are in line with their condition, encouraged to think about what is best for them, so that they can achieve happiness in this world and the hereafter). Inhibiting factors that occur in communication in conveying language are very difficult and also difficult to understand, so guidance must be repeated. The success of guidance is seen in the improvement of emotional development or better behavior exhibited by children with special needs both in the school environment and outside the school environment by conducting Islamic counseling guidance in preventing aggressive behavior towards solutions to the problems faced by children with special needs.